14 Underutilisation of thrombolysis in the national ACS programme; the St James experience. (October 2018) - Yearoo, I; Teehan, S; Hennessey, B; Fitzpatrick, N; Brennan, A; Brandon, L; Alshammari, B Kerr M; Srinivas, P; Daly, C; Crean, P; Cosgrave, J; Murphy, R
Abstract : Optimal reperfusion in STEMI is the key goal of the National ACS programme. The aims of the programme are a diagnosis to door time (DDT) of <90 min and a reperfusion time (RT) of <120 min, with a goal of Primary PCI (PPCI) as the method of reperfusion in over 80% of STEMIs. Thrombolysis is an important reperfusion strategy where primary PCI cannot be offered to STEMI patients within recommended timelines. The aim of this study was to examine the number of patients outside the recommended time goals being referred to St James from other hospitals and hence to estimate the potential patient cohort that should be considered for thrombolysis prior to transfer to the Primary PCI centre. We used the Code STEMI database collected prospectively and HIPE data to identify our patient cohort. From October 2016 to October 2017, 480 patients in total were identified as diagnosed with a STEMI or transferred to St James as part of the National ACS programme. Looking at all-comers; 176 (37%) were transferred from another hospital, 273 (57%) from the field, 31 (6%) from our ED and hospital. The average DDT of the patients from outside hospitals was 130 min (median 110, range 25–645), 64% were outside the 90 min DDT. The average RT was 150 min (median 130, range 37–665), 60% of the patients were outside the recommended 120 min for RT. Only 7 patients (4%) were thrombolysed prior to transfer. There are inevitable delays when arranging transfer of Code STEMI patients from an outside hospital to the primary PCI centre. It is expected that a proportion of patients will have to undergo thrombolysis as the initial reperfusion strategy. The data we collected in the largest PPCI centre in the country highlights that thrombolysis is being under-utilised and needs to be considered in all inter-hospital STEMI transfers.